2021
DOI: 10.1177/15248399211061132
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Health Education Intervention to Improve Parental Knowledge and Attitudes About Chronic Stress and Depression Among Head Start Families

Abstract: Background. Chronic stress and depression disproportionately affect families experiencing poverty, and likely contribute to disparities in early childhood developmental outcomes. Developing strategies to address chronic stress and depression may help mitigate these disparities. Early Head Start (EHS) and Head Start (HS) programs provide an important platform to address the disproportionate burden of stress and mental health issues experienced by EHS/HS families. However, few low-literacy, broad, scalable inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Using TTT educational materials co-developed by community-academic partners and delivered by “trusted locals” was an effective model to engage and teach participants. Previous evidence also demonstrated that TTT is a useful health education tool and format for sustained community-based education 13-15 . Similar to this study, Guerrero et al 15 described the effectiveness of using low-literacy educational materials such as slides, a brochure, and handouts.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Using TTT educational materials co-developed by community-academic partners and delivered by “trusted locals” was an effective model to engage and teach participants. Previous evidence also demonstrated that TTT is a useful health education tool and format for sustained community-based education 13-15 . Similar to this study, Guerrero et al 15 described the effectiveness of using low-literacy educational materials such as slides, a brochure, and handouts.…”
Section: Discussionsupporting
confidence: 78%
“…Previous evidence also demonstrated that TTT is a useful health education tool and format for sustained community-based education 13-15 . Similar to this study, Guerrero et al 15 described the effectiveness of using low-literacy educational materials such as slides, a brochure, and handouts. In addition, the findings of this study and previous literature suggest that videos may improve health literacy challenges 9,13 …”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Parents immigrating to the United States from Korea recently reported increased stress if they encountered language barriers or could not meet their child's educational needs [13 ▪ ,3 ▪▪ ]. Local action to ameliorate parental stress, centered in early childhood educations centers, has been shown recently to reduce caregiver stress and depression levels [14 ▪ ]. Parental education access is especially key as it relates to immigrant and adolescent parents.…”
Section: Introductionmentioning
confidence: 99%